Medical physiology has its own identity as a separate subject - Iqbal, Tehseen (Pakistan Journal of Physiology, 2019)
Medicine is the art and science of healing human diseases. Any branch of biological sciences when comes to help and is related to understanding, preventing, alleviating and curing human diseases becomes ‘Medical’. Medical Physiology deals with how the human body works, depending upon how the individual body systems function, which in turn depend on how the component cells function, depending upon the interactions among subcellular organelles and countless molecules. Graduating medical students believe that physiology is highly relevant and important to their clinical training. About 150 years ago, many authors started writing important Physiology books keeping in view the special needs of medical students, and that established medical physiology as a separate subject.